Consumer protection in India : policies and case studies - Misra, Suresh; Chadah, Sapna; Pathania, Mamta (Concept Pub. Co., 2012)
Papers presented at the National Seminar on "Consumer Protection in India : Lessons Learnt and Future Challenges", held at New Delhi in November 2009.